Novel bithienyl-benzimidazoles: one-pot synthesis and optical and solvatochromic studies - Batista, Rosa Maria Ferreira (2017)
Benzimidazoles are a group of heterocyclic compounds which have been applied in numerous aspects of science and technology. As a result of their interesting electronic and optical properties when incorporated in push-pull systems, benzimidazole derivatives found application as solvatochromic and fluorescent probes, chemosensors, organic light emitting diodes (OLEDs) and non-linear optical (NLO) chromophores.[1] In the last decade our research group has reported experimental and theoretical results regarding the auxiliary donor/acceptor effect of electron deficient benz-X-azole derivatives in push-pull systems.[1b-c, 1e, 1g-i] In this work we describe the synthesis, UV-visible absorption, fluorescence and solvatochromic studies of a series of heterocyclic chromophores of the benzimidazole type. These new bithienyl-benzimidazoles were synthesised in good to excellent yields, by metal-free one-step reaction of o-nitroanilines in the presence of formyl-bithiophenes, via a reductive cyclization, and their optical and solvatochromic properties were evaluated in solvents of different character.